Volume 7B: Structures and Dynamics 2013
DOI: 10.1115/gt2013-94923
|View full text |Cite
|
Sign up to set email alerts
|

Elastomer O-Rings as Centering Spring in Squeeze Film Dampers: Application to Turbochargers

Abstract: This study addresses the nonlinear dynamic behavior of O-ring seals as the centering spring in squeeze film dampers. An analytical model is developed to predict the restoring and hysteresis characteristics of elastomer O-rings and extends the existing models to non-axisymmetric load conditions. Also, the inclusion of axial seals increases the damping capacity of squeeze film dampers. O-rings forces are investigated for different sizes, installation preloads, and operating conditions and contrasted with squeeze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The O-ring under test (1) is compressed between bushing (2), connected to the stinger of shaker (7), and shaft (3), fixed to support (5). The load cell (4) is placed between support (5) and the fixed frame (6). By means of the shaker a sinusoidal displacement is imposed to the bushing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The O-ring under test (1) is compressed between bushing (2), connected to the stinger of shaker (7), and shaft (3), fixed to support (5). The load cell (4) is placed between support (5) and the fixed frame (6). By means of the shaker a sinusoidal displacement is imposed to the bushing.…”
Section: Methodsmentioning
confidence: 99%
“…O-rings were used in gas bearings to improve the static stiffness [2], but in most cases their main function is to overcome the whirl instability in journal bearings [3,4] or the pneumatic hammer [5]. In [6,7] an analytical model is developed to predict the restoring and hysteresis characteristics of elastomer O-rings mounted in squeeze film dampers. Stiffness and damping coefficients of the elastic supports which ensure the stability of the rotor are theoretically studied in [8], where it is shown that it is possible to avoid the half-speed whirl.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its dynamic properties are necessary for mechanical designers, so various types of O-ring were tested, and the measured stiffness and damping coefficients were modeled as functions of temperature, frequency, squeeze, and so on. 1013 Shoyama 14 clarified that the essential shape-independent parameter to derive the mechanical properties of the O-ring is the shear complex modulus of the rubber material, which can be obtained as a function of the deformation frequency and hydrostatic pressure by a previously proposed method. 15…”
Section: Introductionmentioning
confidence: 99%
“…Dult [22] presented the development of preliminary equations by using differential operator algebra to analyze the motion of a simple viscoelastic rotor-shaft-system. Dousti et al [23] addressed the nonlinear dynamic behavior of O-ring seals as the centering spring in the squeeze film dampers, and the model was incorporated in a linear and time transient rotor dynamic analyzer of a vertical turbocharger. Waumans et al [24] used elastomeric O-rings in combination with a tunable squeeze film damper as the elastomer suspension in the experimental test to solve the dynamic stability problem of high-speed air bearings.…”
mentioning
confidence: 99%